2005
DOI: 10.1364/ol.30.000699
|View full text |Cite
|
Sign up to set email alerts
|

All-optical switching and routing based on an electromagnetically induced absorption grating

Abstract: An electromagnetically induced absorption grating is formed in a three-level atomic vapor under the condition of electromagnetically induced transparency in which the strong coupling beam is replaced by a standing wave. The transmission and reflection behaviors of the weak probe beam are greatly modified at certain frequencies near the two-photon resonance. An all-optical two-port signal router-all-optical switch is demonstrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
158
0
5

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 252 publications
(167 citation statements)
references
References 13 publications
4
158
0
5
Order By: Relevance
“…For experimental realization room-temperature and ultracold atoms or ions as well as molecular gases can be used. These experiments are similar to [14]. Hollow-core photonic crystal fibers filled with atoms can be used to reduce the pump and control field intensity requirements.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…For experimental realization room-temperature and ultracold atoms or ions as well as molecular gases can be used. These experiments are similar to [14]. Hollow-core photonic crystal fibers filled with atoms can be used to reduce the pump and control field intensity requirements.…”
Section: Discussionsupporting
confidence: 55%
“…It has been proposed to induce spatially periodic quantum coherence for generation of a tunable PBG [6][7][8][9][10] and dynamic generation of stationary light pulses [11][12][13]. These structures are also referred to as electromagnetically induced absorption gratings (EIAG) [14] or electromagnetically induced gratings [15]. Many researchers have been focused on the study of EIAG [14][15][16][17][18][19][20][21][22][23], that are based on EIT, with their potential applications in mind.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…11,12 In most semiconductor devices optical switching is conceived as an exploitation of optical saturation-though an alternative method, based on quantum interference in electromagnetic induced transparency ͑EIT͒, [13][14][15] has recently been demonstrated in rubidium atoms. [16][17][18] Furthermore, in a novel development by Dawes et al 19 ͑based on the same medium͒, counterpropagating laser beams have been shown to induce an optical pattern that rotates on application of a switching laser.…”
Section: Introductionmentioning
confidence: 98%
“…EIG has been experimentally demonstrated in cold atoms [25,26] and has been applied to all optical switching and routing in hot atomic vapors [27]. Here, we show that, by spatially modulating the control beams, alternating regions of high transmission and absorption can be created inside the atomic sample that act as an amplitude grating and by which the joint Stokes and anti-Stokes wave packet can be shaped.…”
Section: Introductionmentioning
confidence: 76%